2012
DOI: 10.1016/j.injury.2011.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Urine matrix metalloproteinases (MMPs) as biomarkers for the progression of fracture healing

Abstract: While the majority of fractures heal normally, it is estimated that ~10% of fractures exhibit some level of delayed or impaired healing. Although radiography is the primary diagnostic tool to assess the progression of fracture healing, radiographic features only qualitatively correlate with tissue level increases in mineral content and do not quantitatively measure underlying biological processes that are associated with the progression of healing. Specific metaloproteinases have been shown to be essential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Immunodetection for MMP-13 expression revealed the presence of a major band at 68 to 70 kDa that was selectively enriched in 143B EMVs (Figure 6 A ). This band is very likely to be the proenzyme form of MMP-13 as previous studies report the detection of the proenzyme or the latent form at 60 to 65 kDa, whereas the active form is detected at 30 to 48 kDa [34], [35].
Figure 6Detection of pro-osteoclastogenic cargo in 143B EMVs by Western blot analysis. Crude lysates of 143B cells (12.5-25 μg) and EMVs (25-40 μg) were analyzed for MMP-1, MMP-13 (A and B), TGF-β, RANKL, and CD-9 (C) expression by Western blot analysis.
…”
Section: Resultsmentioning
confidence: 85%
“…Immunodetection for MMP-13 expression revealed the presence of a major band at 68 to 70 kDa that was selectively enriched in 143B EMVs (Figure 6 A ). This band is very likely to be the proenzyme form of MMP-13 as previous studies report the detection of the proenzyme or the latent form at 60 to 65 kDa, whereas the active form is detected at 30 to 48 kDa [34], [35].
Figure 6Detection of pro-osteoclastogenic cargo in 143B EMVs by Western blot analysis. Crude lysates of 143B cells (12.5-25 μg) and EMVs (25-40 μg) were analyzed for MMP-1, MMP-13 (A and B), TGF-β, RANKL, and CD-9 (C) expression by Western blot analysis.
…”
Section: Resultsmentioning
confidence: 85%
“…Other studies also showed that high levels of serum MMPs were related with loosening of total hip replacement implants [24]–[25]. In addition, a recent study suggests that urinary levels of MMP-9 and MMP-13 may have potential as metabolic markers to monitor the progression of fracture healing [26].…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that some but not all MMPs may be essential for driving cartilage callus remodeling, others more specifically involved in bone resorption by osteoclasts . After numerous investigations pinpointed a role for MMPs during endochondral fracture repair, recent attention has turned to how MMP levels can be used clinically to assess the progression of fracture repair …”
Section: Discussionmentioning
confidence: 99%